A patient‐oriented risk–benefit analysis of pathogen‐inactivated blood components: application to apheresis platelets in the United States. Issue 7 (15th October 2012) - Kleinman, Steven; Reed, William; Stassinopoulos, Adonis
<x xml:space="preserve">Abstract</x> We performed a risk–benefit analysis for implementation of pathogen‐inactivated (PI) apheresis platelets (APs) in the United States, focusing on the amotosalen/ultraviolet‐A system. Risks and benefits were quantified per patient assuming a mean of 6 AP units per treatment cycle and using available clinical data, mathematical modeling, and observational studies. Current risks associated with AP transfusion can be divided into known partially addressed risks, known well‐addressed risks, and unknown risks associated with acute or chronic emerging infectious agents (EIAs). Bacterial contamination dominates the first category, at a per‐patient rate of 1:250, which correlates with an estimated septic transfusion reaction rate of 1:1000. Quantitation of per‐patient EIA risk was modeled to be between 1:370 (acute) and 1:667 (chronic). Due to its broad range of action PI is expected to reduce or eliminate these infectious risks and also to reduce the rate of febrile transfusion reactions and possibly alloimmunization. These benefits are weighed against 1) concerns for excess bleeding, 2) an apparent increase in acute respiratory distress syndrome in the initial report of the SPRINT clinical trial, and 3) the possible toxicity associated with the introduction of a new chemical into platelet (PLT) units. However, transfusion of an estimated 100, 000 patients with PI PLTs worldwide has occurred without reported serious adverse effects. We conclude that evidence indicates a favorable risk–benefit profile for the implementation of PLT PI and argues for a path forward toward US regulatory approval.